Environmental Biotechnology Research Group: Research Report. - Faculty of Biotechnology & Biomolecular Sciences, Environmental Biotechnology Research Group (Environmental Biotechnology Research Group, 2010)
Environmental biotechnology exploits living organisms (plant, bacteria, fungi, etc) in various applications of waste treatment and remediation of pollutants. The organisms that demonstrate the potential to utilize the wastes or pollutants as food are naturally found in the environment. Rapid development in genetic technology also assists in introducing genetically modified organisms with enhanced capability to degrade wastes or pollutants. It has been proven that environmental biotechnology can provide safer methods of cleaning hazardous wastes compared to conventional methods since it uses natural agents. Finally the utilization of biowastes and organic residues to useful value added product were also studied